Insulin Enhances Post-translational Processing of Nascent SREBP-1c by Promoting Its Phosphorylation and Association with COPII Vesicles - Yellaturu, Chandrahasa R. (American Society for Biochemistry and Molecular Biology, 2009)
The regulation of lipid homeostasis by insulin is mediated in part by the enhanced transcription of the gene encoding SREBP-1c (sterol regulatory element-binding protein-1c). Nascent SREBP-1c is synthesized and embedded in the endoplasmic reticulum (ER) and must be transported to the Golgi in coatomer protein II (COPII) vesicles where two sequential cleavages generate the transcriptionally active NH(2)-terminal fragment, nSREBP-1c. There is limited indirect evidence to suggest that insulin may also regulate the posttranslational processing of the nascent SREBP-1c protein. Therefore, we designed experiments to directly assess the action of insulin on the post-translational processing of epitope-tagged full-length SREBP-1c and SREBP-2 proteins expressed in cultured hepatocytes. We demonstrate that insulin treatment led to enhanced post-translational processing of SREBP-1c, which was associated with phosphorylation of ER-bound nascent SREBP-1c protein that increased affinity of the SREBP-1c cleavage-activating protein (SCAP)-SREBP-1c complex for the Sec23/24 proteins of the COPII vesicles. Furthermore, chemical and molecular inhibitors of the phosphoinositide 3-kinase pathway and its downstream kinase protein kinase B (PKB)/Akt prevented both insulin-mediated phosphorylation of nascent SREBP-1c protein and its posttranslational processing. Insulin had no effect on the proteolysis of nascent SREBP-2 under identical conditions. We also show that in vitro incubation of an active PKB/Akt enzyme with recombinant full-length SREBP-1c led to its phosphorylation. Thus, insulin selectively stimulates the processing of SREBP-1c in rat hepatocytes by enhancing the association between the SCAP-SREBP-1c complex and COPII proteins and subsequent ER to Golgi transport and proteolytic cleavage. This effect of insulin is tightly linked to phosphoinositide 3-kinase and PKB/Akt-dependent serine phosphorylation of the precursor SREBP-1c protein.